A first course in abstract mathematics - Mostafazadeh, Ali (İstanbul : Koç Universiy Press, 2011)
Contents
Keywords: Proof theory Abstract mathematics Logic, Symbolic and mathematical; Proof teorisi Soyut Matematik Mantık, Sembolik ve matematiksel